Compound Cavity Passively Q-Switched Single-Longitudinal-Mode Diode-Pumped Laser - Chen, Bin; Bai, Zhenxu; Zhao, Guijuan; Zhang, Yu; Yan, Bingzheng; Qi, Yaoyao; Ding, Jie; Wang, Kun; Wang, Yulei; Lu, Zhiwei (Frontiers in Physics, 2022)
A compact solid-state single-longitudinal-mode (SLM) Q-switched laser based on a compound cavity is demonstrated. SLM operation is achieved through the enhancement of mode competition (via manipulation of the effective reflectivity of the resonator mirrors and intracavity field accumulation time) and does not require the use of a feedback loop. In this work, SLM emission with a linewidth of 254.3 MHz is demonstrated, and a high SLM ratio of up to 99.6% is achieved. The laser operates at a repetition rate of 10 Hz, producing 10 ns pulses with a pulse energy of 14.81 mJ.